DEMOGRAPHIC BONUS AND HUMAN RESOURCE READINESS OF INDONESIA'S YOUNG GENERATION - Olimpius Kurniawan (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article examines Indonesia’s demographic dividend and the readiness of its young human resources by focusing on the availability of formal employment and the alignment between higher education graduates and labor market demand. The study applies a descriptive qualitative approach based on a systematic literature review, secondary data, and SWOT analysis. Data were drawn from publications of Statistics Indonesia, higher education policy documents, and scholarly literature related to demographic dividend, employment, and education. The findings show that Indonesia has strong demographic capital through its large productive age population and massive higher education enrollment, yet its potential remains constrained by educated unemployment, unequal access to formal jobs, and mismatch between educational attainment and labor market needs. Labor data in 2025 indicate that graduates from vocational secondary schools and universities still face relatively high unemployment, while formal employment opportunities remain concentrated in urban areas and specific social groups. This condition suggests that the demographic dividend does not automatically translate into economic gains. Strengthening the link and match between higher education, skill development, and the needs of industry and business sectors is therefore essential. In conclusion, the successful utilization of Indonesia’s demographic dividend depends on the state’s ability to create formal, relevant, inclusive, and sustainable jobs for young people in support of Golden Indonesia 2045.